Out of the Dark: Samuel Beckett and BBC radio - Chignell, Hugh (Peripeti, 2015)
Samuel Beckett was one of the most influential and famous cultural figures of the twentieth century and his radio contribution is significant. This article recognises both work written for radio as well as readings from novels and adaptations of stage plays. His acceptance at the BBC was problematic but made possible by the creation of the Third Programme.